The Student Anxiety Level and the Dominant Factors Influencing in Learning English at SMKN 17 Samarinda - Taufik Hidayat; Masrur Yahya; Weningtyas Parama Iswari (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2019)
Anxiety in learning English is a state of tension and apprehension as a natural response in learning English, and might impede students’ learning process. This study was intended to find the students anxiety level and the dominant factor influencing in learning English. The survey research was applied to get the data needed. There were 120 respondents from four classes of the eleventh grade students of SMKN 17 Samarinda. The research instrument was a questionnaire by Horwitz (1991). Descriptive statistics was used to analyze the quantitative data. It was found out that on average students had high anxiety level, in which 73% of the students were categorized as having high anxiety level. Then, 19 % of the students had very high anxiety level, and 7.5% had medium anxiety. There are three anxiety factors, two factors: communication apprehension (74.9%) and test anxiety (74,5%) became the dominant factors, since in both factors, while the negative evaluation (69%) was the lower percentages from three dominant factor. Moreover, there were sub-factors which were found in this study that had correlation with the dominant factors in learning English, such as: not confident in learning English and lack of vocabulary (communication apprehension), teacher did not reduce anxiety and teaching quickly (test anxiety) and not good environment in learning English (fear negative evaluation)